Teenage childbearing and labor market implications for women - Phillip B. Levine (IZA World of Labor, 2014)
It is not difficult to find statistics showing that teenage childbearing is associated with poor labor market outcomes, but why is this the case? Does having a child as a teenager genuinely affect a woman's economic potential—or is it simply a marker of problems she might already be facing as a result of her social and family background? The answer to this question has important implications for policy measures that could be taken to improve women's lives.
Keywords: J13; 330; teen fertility; education; wages; income